Breast reconstruction with the free TRAM or DIEP flap – What is the current standard? Consensus Statement of the German Speaking Working Group for Microsurgery of the Peripheral Nerves and Vessels - Eisenhardt, Steffen U.; Momeni, Arash; Von Fritschen, Uwe; Horch, Raymund E.; Starks, G. Bjoern; Bannasch, Holger; Harder, Yves; Heitmann, Christoph; Kremer, Thomas; Rieger, Ulrich M.; Kneser, Ulrich (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2018)
The most common donor-site for autologous breast reconstruction is the abdomen. Over the past several decades technical advances have resulted in the development of flaps that have been associated with a progressive decrease in abdominal wall morbidity. However, controversy exists related to the differences between muscle-sparing (MS)-TRAM and deep inferior epigastric perforator (DIEP) flaps. Hence, the question which approach should be considered standard of care remains unanswered. To address this question the current literature and published evidence was critically reviewed and discussed by an expert panel at the 39th Annual Meeting of the German-speaking Society for Micro surgery of the Peripheral Nerves and Vessels (DAM). Based on this discussion a consensus statement was developed that incorporates contemporary data regarding postoperative complication rate, donor site morbidity, as well as expert opinion regarding technical details in autologous breast reconstruction with free TRAM and DIEP flaps.
EVALuna2:211474